Phytotherapy in Liver Diseases - Adem AKÇAKAYA (Bezmiâlem Science)
The liver is the largest internal organ in the body and has vital functions such as metabolism, elimination of toxins, and bile production. Liver diseases include various conditions that affect the functions of this organ. The most common liver diseases include hepatitis, cirrhosis, fatty liver disease, and liver cancer. These diseases can develop due to genetic factors, alcohol consumption, viral infections, and obesity. A healthy lifestyle is of great importance in preventing liver diseases. Measures such as a balanced diet, regular exercise, limiting alcohol consumption, and protection from viral infections (e.g., vaccinations) help protect liver health. In addition, avoiding exposure to toxins is also important. Interest in phytotherapy has increased considerably in recent years, except for medical applications, in the protection of liver health and the treatment of liver diseases. Among the plants used for this purpose, foods such as artichoke, pomegranate, grapes, and grapefruit, teas such as chamomile, or extracts containing active ingredients such as ellagic acid, resveratrol, and curcumin can be listed. This article will discuss the effects of some plants on liver health. In addition to the plants mentioned here, many other plants are used in this area. While plants are beneficial when used in food format for general health, if they are used for treatment purposes and as an extract, they should be used under the supervision of a physician who has received phytotherapy training. As a result, liver diseases can be prevented, and when they do occur, most of them can be treated. A healthy lifestyle, regulating habits, healthy choices in food intake, and herbal supplements can play an important role in this process.